Educational Alimony for Wives: A Study of Jasser Auda's Maqāshid As-Syariah - Abdillah Afabih; Imam Annas Mushlihin; Yayan Musthofa; M. Rizki Syahrul Ramadhan; Muhammad Alamudin (UIN Sunan Gunung Djati Bandung, 2026)
This study re-examines the concept of wives' financial maintenance (nafaqah) in Islamic law, with a specific focus on its educational component. While classical jurisprudence and The Compilation of Islamic Law (KHI) acknowledge basic needs, the allocation for spousal education within the official Decent Living Standard (KHL) remains minimal. Employing Jasser Auda's maqāṣid al-shariah and his systems approach as an analytical framework, this article argues for a paradigm shift. It demonstrates that a broader interpretation of mafqadah, informed by Auda's six systemic elements—cognitive nature, wholeness, openness, interrelated hierarchy, multi-dimensionality, and purposefulness—necessitates prioritizing and increasing the educational allotment in nafaqah. This re-conceptualization aligns with the higher objectives of Sharia in fostering human development (tanmiyah al-basyariyah) and building a resilient family system. The study contributes to the contemporary maqāṣid discourse and offers policy implications for reforming living standard calculations in Muslim-majority societies.